Evaluation of Digital Maturity Level of Citra Husada Jember Hospital as a Strategy to Support Health Transformation - Dewa Ngakan Gde Wahyu Mahatma Putra; Khrisna Agung Cendekiawan; Lutvi Anggraeni Anggraeni (Jurnal teknologi Kesehatan Borneo, 2025)
The digital transformation of healthcare services demands hospital readiness in adopting integrated information systems. This study aimed to assess the digital maturity level of RS Citra Husada Jember using the Digital Maturity Instrument version 1.1 from the Ministry of Health of the Republic of Indonesia which includes seven main components: information systems and infrastructure, standards and interoperability, management and governance, data analysis, human resources, information security, and utilisation of electronic medical records and patient-centred services. This study used a descriptive cross-sectional design involving six internal hospital stakeholders through structured discussions. Results showed good digital maturity, with the highest scores in management and governance (4.5) and EMR (4.3), while the lowest scores were found in external interoperability (1.7) and data analytics. These findings emphasise the importance of strengthening digital infrastructure, improving digital literacy of health workers, and system integration to support the national OneHealth policy.